Viscoelastic behavior, deformation, and rupture of cells - Tan, Samuel Chun Wei (2011)
In this study, the effects of tensile stress on single cells were examined at both the cellular and subcellular levels in terms of global and local deformation, based on the application of micropipette aspiration. At the cellular level, the global deformation behavior of human mesenchymal stem cells (hMSCs) was studied in relation to temperature effect and the structural integrity of actin filaments. hMSCs were found to possess the characteristics of a viscoelastic solid material which can be described by a sudden increase in length at the initial aspiration time before gradually reaching an equilibrium length over time. In addition, there were three other types of non-typical viscoelastic behaviors. Based on the three-parameter viscoelastic model, the instantaneous and equilibrium Young's moduli at 20oC were calculated as 886 ± 289 Pa and 372 ± 125 Pa, respectively while the apparent viscosity of hMSCs was recorded as 2700 ± 1600 Pa.s. By disrupting the F-actin filaments of hMSCs using cytochalasin D with a concentration up to 20 µM, the stiffness of hMSCs decreased drastically by up to 84% and the viscosity experienced a large increase by up to 255%. Compared to the results obtained at 20oC, the stiffness of hMSCs at 37oC was found to be significantly reduced by 42 – 66% while there was a 95% increase in viscosity. These findings demonstrate that the stiffness and viscosity of hMSCs are dependent on the structural integrity of F-actin filaments and temperature.